The Influence of workload, job satisfaction and commitment. organization.against.kinerja.implementing nurses at Padang Reksodiwiryo Hospital - Mardhatila Fitri Sopali; Ai Elis Karlinda (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The main purpose of this research is to see how big the impact of Employee Performance, Workload, Job Satisfaction and Organizational Commitment on the Performance of Implementing Nurses at Reksodiwiryo Hospital Padang. The steps taken in this research are direct surveys and distributing questionnaires to all nurses in the hospital environment, the number of which will be examined is 60 respondents from the Nurse Practitioner at the Tk Hospital. III Dr. Reksodiwiryo Padang. This research uses multiple regression analysis system. The conclusions obtained based on the partial test (t test) are: (a) there is an influential relationship between the workload variable on the performance of the implementing nurse. The result is that Ho is rejected, Ha is accepted. (b) there is a significant relationship between the variables of Job Satisfaction on the Performance of Implementing Nurses. In the results obtained, Ho is rejected, Ha is accepted. (c) there is an influential relationship between Organizational Commitment to the Performance of Implementing Nurses. In the final result, Ho is rejected, Ha is accepted. (d) together work, job satisfaction and organizational commitment have a significant effect on the performance of implementing nurses. So the author concludes that workload, job satisfaction and organizational commitment simultaneously and partially affect the performance of implementing nurses. And based on the coefficient of determination test (R2) the value is 0.700. (e) The contribution of the variables of Workload, Job Satisfaction and Organizational Commitment simultaneously and partially to Improving the performance of implementing nurses is 70% and 30% is influenced by other variables outside this study.